2014
DOI: 10.1016/j.ecolecon.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental policy instruments on innovation: A review of energy and automotive industry studies

Abstract: Various types of policy instruments have been implemented to reduce local and global emissions, but the impact on innovation of different instruments has received less attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(107 citation statements)
references
References 89 publications
1
101
0
5
Order By: Relevance
“…However, under strong assumptions, the uncertainty in the cost function increases the superiority of the price instrument [11]. 6 Using different assumptions, others have suggested that there is no instrument strictly better than the other and that the policy application should be "time-dependent" [12]. Similarly, the advantage of one instrument over the other depends on how correlated the uncertainty in the benefits and costs function [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under strong assumptions, the uncertainty in the cost function increases the superiority of the price instrument [11]. 6 Using different assumptions, others have suggested that there is no instrument strictly better than the other and that the policy application should be "time-dependent" [12]. Similarly, the advantage of one instrument over the other depends on how correlated the uncertainty in the benefits and costs function [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence which suggests that the choice of instrument has possible implications on technological innovation [4] [5] [6]. 2 This suggests that the regulator may incur a political gain if the choice of instrument increases the incentives for industry to invest in cleaner technology.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of ISO 50001 implementation, companies tend to focus on reducing their environmental impact through the implementation of the Environmental Management System (EMS) ISO 14001, mainly because of the tightening of international environmental standards [15][16][17][18]. In 2015, 319,324 ISO14001 certificates were issued, but in the same year, only 11,985 accreditations in ISO 50001 were issued (despite a remarkable increment of 77% compared to 2014) [19].…”
mentioning
confidence: 99%
“…supporting grants or tax reductions for companies willing to develop new products or services), or to induce the diffusion of innovations (e.g. investment subsidies to encourage actors to buy an innovation, measures affecting relative prices such as guaranteed purchase prices for products produced from a certain technology) (Bergek et al, 2014).…”
Section: Adoption Drivers During the Large-scale Diffusion Of Innovationmentioning
confidence: 99%
“…Authors have also suggested strategies aimed at lowering systemic challenges (e.g. Bergek et al, 2014Bergek et al, , 2008b. Nevertheless, the fact that adopters, despite a variety of both systemand actor-level problems, still manage to implement their adoption decisions suggests that they also develop individual strategies.…”
Section: Introduction To Key Conceptsmentioning
confidence: 99%